Source-Agent-Client Components in Strategic Information Systems Planning Methodology for Malaysian Public Sector - Abdul Wahab, Muhammad Nubli (2004)
Strategic information systems planning (SISP) remains a primary concern for many organizations due of its importance. However, the implementation of this concept has raised some doubts because it is unable to achieve it's organizational benefits. Major problems towards this are related to human factors such as lack of commitment and involvement among organizational members in the SISP process. This research propose additional elements in SISP methodology by introducing “source”, “agent” and “client”. The characteristics of these elements and their good interaction help to develop the awareness and readiness among organizational members towards SISP activities. The survey that is conducted among 72% of Malaysian ministries, has proven that the proposed elements are important in the SISP development process. Results from in-depth interviews with SISP practitioners have also proven that the instilment of awareness and readiness are among the important processes in SISP. Tests on the applicability of the proposed SISP elements, combined with existing SISP methods involving 2 public sector organization show their applicability with the test score up to 94%. This research concludes that the proposed SISP elements are important and applicable for the public sector in Malaysia.